A simple way to improve the security of Bluetooth devices - Dell, Peter; Ghori, Khwaja Shan-ul-Hasan (IEEE Computer society Conference Publishing Services (CPS), 2008)
Bluetooth is a de facto standard feature in mobile devices such as smart phones, PDAs and similar devices. While this provides great convenience to the user, there are a number of security issues for which exploits are widely available. This fact, combined with the growing sophistication of devices, creates the potential for serious loss in the event of a security breach. This paper investigates the use of Bluetooth profiles by the public and finds that some potentially high-risk profiles are not widely used. A subsequent investigation of a number of devices determined that no way of configuring individual profiles was available. The paper concludes with a recommendation that devices allow users to configure individual Bluetooth profiles.